Nitric oxide-mediated sensitization of resistant tumor cells to apoptosis by chemo-immunotherapeutics() - Bonavida, Benjamin (Redox Biol, 2015)
The generation of NO by the various NO synthases in normal and malignant tissues is manifested by various biological effects that are involved in the regulation of cell survival, differentiation and cell death. The role of NO in the cytotoxic immune response was first revealed by demonstrating the induction of iNOS in target cells by immune cytokines (e.g. IFN-γ, IL-1, TNF-α, etc.) and resulting in the sensitization of resistant tumor cells to death ligands-induced apoptosis. Endogenous/exogenous NO mediated its immune sensitizing effect by inhibiting NF-κΒ activity and downstream, inactivating the repressor transcription factor YY1, which inhibited both Fas and DR5 expressions. In addition, NO-mediated inhibition of NF-κΒ activity and inhibition downstream of its anti-apoptotic gene targets sensitized the tumor cells to apoptosis by chemotherapeutic drugs. We have identified in tumor cells a dysregulated pro-survival/anti-apoptotic loop consisting of NF-κB/Snail/YY1/RKIP/PTEN and its modification by NO was responsible, in large, for the reversal of chemo and immune resistance and sensitization to apoptotic mechanisms by cytotoxic agents. Moreover, tumor cells treated with exogenous NO donors resulted in the inhibition of NF-κΒ activity via S-nitrosylation of p50 and p65, inhibition of Snail (NF-κΒ target gene), inhibition of transcription repression by S-nitrosylation of YY1 and subsequent inhibition of epithelial–mesenchymal transition (EMT), induction of RKIP (inhibition of the transcription repressor Snail), and induction of PTEN (inhibition of the repressors Snail and YY1). Further, each gene product modified by NO in the loop was involved in chemo-immunosensitization. These above findings demonstrated that NO donors interference in the regulatory circuitry result in chemo-immunosensitization and inhibition of EMT. Overall, these observations suggest the potential anti-tumor therapeutic effect of NO donors in combination with subtoxic chemo-immuno drugs. This combination acts on multiple facets including reversal of chemo-immune resistance, and inhibition of both EMT and metastasis.